Isolation optimisation, synthesis, molecular docking and in silico ADMET studies of lantadene a and its derivatives. Issue 21 (2nd November 2021) - Suthar, Sharad Kumar; Hooda, Ajay; Sharma, Ankesh; Bansal, Sumit; Monga, Jitender; Chauhan, Monika; Sharma, Manu
Abstract: A simple and economical method was developed for the extraction and isolation of pentacyclic triterpenoid lantadene A from the leaves of Lantana camara . The lantadene A displays significant anti-inflammatory and anticancer properties via the inhibition of IKK-mediated NF-κB protein. Therefore, the derivatives of lantadene A were synthesised to further optimise the pharmacophore for anti-inflammatory and anticancer activities. The synthesised compounds were docked into the active site of IKK to find the most potent inhibitor of IKK. Molecular docking studies revealed that 3 β, 22 β -diisobutyl substituted lantadene derivative (10 ) binds to the IKK protein with the highest affinity. Furthermore, in the in silico ADMET studies, the lead IKK inhibitor (10 ) was found to be Ames non-toxic, non-carcinogen, and a weak inhibitor of hERG.